1998
DOI: 10.1086/300499
|View full text |Cite
|
Sign up to set email alerts
|

Observational Evidence from Supernovae for an Accelerating Universe and a Cosmological Constant

Abstract: We present spectral and photometric observations of 10 type Ia supernovae (SNe Ia) in the redshift range 0.16 ≤ z ≤ 0.62. The luminosity distances of these objects are determined by methods that employ relations between SN Ia luminosity and light curve shape. Combined with previous data from our High-Z Supernova Search Team (Garnavich et al. 1998;Schmidt et al. 1998) and Riess et al. (1998a), this expanded set of 16 high-redshift supernovae and a set of 34 nearby supernovae are used to place constraints on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

378
12,068
15
121

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 17,022 publications
(12,582 citation statements)
references
References 115 publications
378
12,068
15
121
Order By: Relevance
“…In two previous works by the author [1] [2], hereafter referred to as I and II, it was shown that it is possible to explain the diminished brightness of the Type Ia supernovae (SNe Ia) found by Perlmutter et al [3] [4], Riess et al [5], and Schmidt et al [6], and the increased distance to the "standard ruler" of the baryon acoustic oscillations (BAO) determined by Anderson et al [7] [8], by assuming that the speed of light through the dark energy of intergalactic space has been reduced to c/n, where n is the index of refraction of the dark energy. Thus, in this alternative model, the dark energy no longer has associated with its energy-momentum source tensor a negative pressure that causes the expansion of the universe to accelerate (for a review see, e.g., Wang [9]), but instead has an index of refraction greater than unity.…”
Section: Introductionmentioning
confidence: 99%
“…In two previous works by the author [1] [2], hereafter referred to as I and II, it was shown that it is possible to explain the diminished brightness of the Type Ia supernovae (SNe Ia) found by Perlmutter et al [3] [4], Riess et al [5], and Schmidt et al [6], and the increased distance to the "standard ruler" of the baryon acoustic oscillations (BAO) determined by Anderson et al [7] [8], by assuming that the speed of light through the dark energy of intergalactic space has been reduced to c/n, where n is the index of refraction of the dark energy. Thus, in this alternative model, the dark energy no longer has associated with its energy-momentum source tensor a negative pressure that causes the expansion of the universe to accelerate (for a review see, e.g., Wang [9]), but instead has an index of refraction greater than unity.…”
Section: Introductionmentioning
confidence: 99%
“…Note that although the title of van den Bergh's 1999 paper is The Early History of Dark Matter, the century long search for Vulcan is entirely overlooked. The most recent purported evidence for dark matter, starting in the last decade of the twentieth century and continuing vigorously today, comes from detailed surveys and analyses of Type Ia supernovae (SNe Ia) [8]- [13] and cosmic microwave background (CMB) anisotropies [7].…”
Section: The Twentieth Centurymentioning
confidence: 99%
“…The supernova distance determined in this way is independent of the recession velocity as determined by the redshift of the host galaxy. These two independent pieces of information, applied statistically to a large sample of type Ia supernovae, revealed the remarkable, and deeply challenging, result that the Universe is accelerating, most often interpreted as the effect of a 'dark energy' [48,49]. The supernova results coupled with other techniques (fluctuations in the cosmic microwave background radiation, the spatial distributions of galaxies and the growth of clusters of galaxies) suggest that this effect is consistent with Einstein's cosmological constant in a Universe that is geometrically flat.…”
Section: (A) Type Ia: Exploding White Dwarfsmentioning
confidence: 99%